Analysis of micro-EDM electric characteristics employing plasma property. (January 2018) - Asad, A.B.M.A.; Islam, M. Tanjilul; Masaki, Takeshi; Rahman, M.; Wong, Y.S.
Abstract: Micro-electro discharge machining (micro-EDM) involves simultaneous complex processes associated with electrical characteristics and plasma properties, which lead to the removal of material from both electrode and workpiece. Unfortunately, existing micro-EDM models are simple electro-thermal based and not capable to connect the link between plasma and electrical circuit. This article presents a theoretical study to model the electric properties of micro-EDM plasma discharge for RC power supply with direct current (DC) source. Analysis presented in this study provides significant insight for realizing changes in the current waveform due to changes in parameters like input voltage, capacitance, inductance and the charging resistance. This research bridges a crucial gap in the present theoretical understanding on the interaction of micro-EDM plasma with different circuit elements of micro-EDM power supply. Furthermore, by employing this proposed model, a novel stray capacitance measurement method has been presented to adjust pulse energy at minimum level for smallest machinable features. The robustness of the analytical model is substantiated by validating it on multiple experimental results of measured data as well as literature data.